(untitled) (Bangladesh Journal of Botany, 2022)
Phytochemical investigation of petroleum ether (PESF) and dichloromethane soluble (DCMSF) fractions designated as PESF and DCMSF, respectively of methanol extract of leaves of Bouea oppositifolia (Roxb. Meisn. (an endangered species of Bangladesh) yielded six compounds, which were characterized as betulin (1), lupeol (2), lupenone (3), stigmasterol (4), p-coumaric acid (5), and oleic acid (6) by high field NMR studies and comparison with published values. The identity of the isolated compounds were further substantiated by co-TLC. Bangladesh J. Bot. 51(1): 185-189, 2022 (March)